Effect of copper and magnesium on the precipitation characteristics of Al-Li-Mg, Al-Li-Cu and Al-Li-Cu-Mg alloys - Katsikis, Spyros (2001)
The effects of copper and magnesium on the precipitation characteristics of Al-Li-Mg, Al-Li- Cu, and Al-Li-Cu-Mg alloys have been investigated during isochronal and isothermal ageing. In AI-Li-Mg alloys, increasing the magnesium concentration results in stimulation of δ'precipitation by a shift of the α/δ'solvus boundary to higher temperatures. It was shown that for each wt%Mg present in the alloy the α/δ'solvus boundary shifts by 7.0°C. In Al-Li-Cu alloys the concentration of copper has no effect on the position of the α/δ'solvus boundary. The significant stimulation of δ' observed in Al-Li-Cu alloys was shown to be due to the formation of GPCu zones that act as heterogeneous nucleation centres. TEM analysis showed that this heterogeneous nucleation produced composite precipitates consisting of an inner plate of GPI zone and an outer cylindrical shell of δ'. At high copper concentrations (Cu>2.0%) and long ageing times at 150°C, significant retardation of δ' precipitation takes place due to precipitation of the equilibrium T1 and T2 phases.